Effects of UV-A/B/C on flavonoids and related synthetic enzymes in Tetrastigma hemsleyanum - Li, Shan; Xia, Jingqing; Liu, Shouzan; Li, Zhe; Shen, Qiong; Yang, Feng; Liu, Xinhong; Bai, Yan (Frontiers in Plant Science, 2024)
Tetrastigma hemsleyanum is a folk and rare medicinal plant, and specifically, it is distributed in the south, China. To investigate the cumulative properties of its medicinal components, we investigated the effect of UV light on the flavonoid contents and related enzyme activity changes in T. hemsleyanum. The leaves and tubers were treated with UV-A, UV-B and UV-C for 1 h, 1L/23D h, 3 h and 3L/21D h (D represents darkness treatment). High Performance Liquid Chromatography (HPLC) analysis showed that content of many flavonoids decreased significantly during UV-A treatment, while it increased after UV-B and UV-C irradiation and accumulated again after darkness treatment. In root tubers of UV-A group, naringin content in 3L/21D h group (0.069 µg/g) was 16.30 times higher than that of 3 h group (0.0042 µg/g). The content of rutin was elevated after UV irradiation, but was not detected in CK group. The test results of Enzyme-linked kit indicated that activities of many enzymes were higher in UV-A and UV-B irradiation than those in CK group, but the results were reversed in UV-C treatment. After darkness treatment, activities of most enzymes were higher than with alone UV irradiation, F3'5'H activity in 3L/21D h group (97.25 U/L) was 1.24 times higher than that in 3 h group (78.12 U/L) in UV-A treated group in leaves. The study results suggested that appropriate UV-B and UV-C irradiation, as well as darkness supplementation, had a promotive effect on flavonoids in the leaves and root tubers of T. hemsleyanum. Additionally, UV irradiation and darkness treatment could enhance the activities of most enzymes.